Tindak Pidana Penistaan Agama Oleh Lina Mukherjee Ditinjau Dari Asas Kepastian Hukum Studi Putusan Nomor : 726/Pid.Sus/2023/PN Plg - Zakiyyah, Faizah; Manik, Jeanne Darc Noviayanti; Agustian, Rio Armanda (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
This research discusses the criminal offense of religious blasphemy committed by Lina Lutfiawati (Lina Mukherjee), as regulated under Article 28 paragraph (2) in conjunction with Article 45A paragraph (2) of Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law). The primary focus of this study is to analyze the judge's decision in Case Number: 726/Pid.Sus/2023/PN Plg through the lens of the legal certainty principle. In this case, the defendant was sentenced to 2 years in prison and fined IDR 250,000,000, or an additional 3 months of imprisonment, for uploading a video in which she recited the basmalah while eating pork—an act considered offensive to Islam. This research adopts a normative juridical approach using qualitative data analysis techniques. The findings show that although the defendant’s actions were perceived to violate religious norms, the severity of the sentence appears to overlook the principles of justice and proportionality. The verdict is considered excessive and does not reflect balanced legal protection, particularly for the defendant, who is also entitled to legal certainty as a citizen. In the context of legal certainty, the decision raises concerns due to the subjective and ambiguous interpretation of the element “inciting hatred.”